2016
DOI: 10.1177/0956247816655986
|View full text |Cite
|
Sign up to set email alerts
|

Technology, informal workers and cities: insights from Ahmedabad (India), Durban (South Africa) and Lima (Peru)

Abstract: The findings reveal that informal workers in the study cities are using diverse tools, from manual devices to electrical equipment and internet platforms, to strengthen their livelihoods. Overall, the tools used tend to be basic. Often they are being adapted in ingenious ways in order to adapt to resource and other constraints. Take-up of improved tools is limited by low incomes and concerns about theft and confiscation. It is also affected by city-level, context-specific systems of energy, transport and waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…There is no generally accepted definition of the SC concept, and the extensive literature published on the subject in recent years – mostly in English and originating in Anglo-Saxon countries (Rose and Willis, 2019; Taylor Buck and While, 2017; Valdez et al, 2018), with the exception of limited work in India (Chakrabarty, 2019; Datta, 2016) and elsewhere (Batista and Fribiuk, 2017; Cai et al, 2020; Chen, 2016; Flórez, 2016; Watson, 2015) – proposes various definitions (Angelidou, 2015). However, despite this conceptual vagueness and the difficulty of isolating it as an object of study (Duque, 2016), the clearest consensus interprets SC as a technology-driven form of urbanisation.…”
Section: Provincialising the Smart City Model In Santiago Chilementioning
confidence: 99%
“…There is no generally accepted definition of the SC concept, and the extensive literature published on the subject in recent years – mostly in English and originating in Anglo-Saxon countries (Rose and Willis, 2019; Taylor Buck and While, 2017; Valdez et al, 2018), with the exception of limited work in India (Chakrabarty, 2019; Datta, 2016) and elsewhere (Batista and Fribiuk, 2017; Cai et al, 2020; Chen, 2016; Flórez, 2016; Watson, 2015) – proposes various definitions (Angelidou, 2015). However, despite this conceptual vagueness and the difficulty of isolating it as an object of study (Duque, 2016), the clearest consensus interprets SC as a technology-driven form of urbanisation.…”
Section: Provincialising the Smart City Model In Santiago Chilementioning
confidence: 99%
“…For those who use the mobile phone, they mainly use instant messaging applications such as WhatsApp to facilitate them with customers. Furthermore, the Focus Group Discussion (FGD) conducted by Chen (2016) revealed that the use of mobile phones among the informal sector workers is for work related and organizing efforts to contact members and organize meetings with the intensity between 5 to 8 (10 scale). The use of the internet for working purposes is much less by only 1 to 5 (10 scale).…”
Section: Urban Poverty and Digital Dividementioning
confidence: 99%
“…Scholars also argue that cities need to be more responsive to the needs of informal workers. Chen’s (2016) study on the uses of technology by informal workers in Lima demonstrates the creative ways in which informal workers use technology and their wealth of knowledge about the city, which could shape better SC initiatives yet go unrecognised (Chen, 2016). The experiences of Bogotá and Medellín demonstrate SC policies circulating worldwide, creating performances as a way of making the ideas visible (Duque, 2016; Franco, 2011).…”
Section: Smart Cities In Latin America:an Overviewmentioning
confidence: 99%